Perbedaan Antara Terapi Fibrinolitik Dan Heparinisasi Terhadap Perubahan St-Elevasi Pada Penderita Infark Miokard Akut Di RSUD Moewardi - Setyawati, Anis; , dr. Sumardjo Sp.PD; , dr. Listiana Masyita Dewi, M.Sc (Universitas Muhammadiyah Surakarta, 2015)
Background. Acute myocardial infarction with ST-elevation (STEMI) was a necrotic area resulted from total occlusion on the blood vessel wall, which lead to accumulation of extracellular K +. Fibrinolytic therapy had a big role solving the thrombus formed, meanwhile heparinization only prevents thrombus extension. Improved occlusion in the blood vessels characterized by decreasing of STelevation. Aim. This study aimed to analyze the difference beetwen fibrinolytic therapy and heprinization to ST-elevation changes in patients with acute myocardial infarction. Method. This study was observational analytic with cross sectional approach. This study was held at the medical record division of RSUD Moewardi in November 2014-January 2015. 50 samples divided into fibrinolytic and heparinization groups. Samples were taken using purposive sampling method. Results. Result from 50 patients had decreased >70% of ST-elevation in 18 patients with fibrinolytic threapy anda 9 patients with heparinization. From Chi-Square test, the p value = 0,011 (<0,05), so there was significant difference of heparinization and fibrinolytic groups. Conclusion. There significant difference between fibrinolytic and heparinization treatment in ST-elevatin changes of acute myocardial infarction in Moewardi General Hospital 2013-2014.